Pengaruh Media Tiktok dan Perubahan Perilaku Konsumen terhadap Keputusan Pembelian pada Toko Offline Putra Kembar Shoes di Kadungora Kabupaten Garut - Ilham Nur Bayani; Iim Takwim (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The decline in the revenue of Putra Kembar Shoes and its delayed TikTok adoption created an urgent need to examine how digital promotion and changing consumer behavior shape purchases in physical stores. This study analyzed the partial and simultaneous effects of TikTok as a marketing medium and changes in consumer behavior on purchase decisions at the Putra Kembar Shoes offline store in Kadungora, Garut Regency. A quantitative explanatory survey design was applied. Questionnaire data were collected from 96 consumers selected through purposive sampling. Eligible respondents had purchased products at the store and viewed TikTok content related to footwear. The data were analyzed using multiple linear regression, partial significance tests, a simultaneous significance test, and the coefficient of determination. The results showed that TikTok as a marketing medium had a positive and significant effect on purchase decisions, with a regression coefficient of 1.074 and a partial test statistic of 98.564. Changes in consumer behavior also had a positive and significant effect, with a regression coefficient of 0.153 and a partial test statistic of 3.479. Simultaneously, both variables significantly affected purchase decisions, with a simultaneous test statistic of 4,882.236. The coefficient of determination was 0.991, indicating that both predictors explained 99.1 percent of the variation in purchase decisions. These findings emphasize the need to integrate consistent TikTok promotion with strategies that address consumers’ online information-search and product-comparison habits. This study contributes empirical evidence on the relationship between social media marketing, consumer behavior change, and offline purchase decisions in a non-metropolitan retail market.